(untitled) (Bangladesh Journal of Botany, 2008)
Essential oils obtained by hydrodistillation from needles, dry needles, inflorescences and resin of Pinus caribaea Morelet were analyzed by GC-MS. Seven chemical constituents in oil of needles, 13 in dry needles, 4 in inflorescences and 6 in resin were identified. The major constituents found in the needle oil are limonene, caryophyllene and germacrene D in the dry needle oil limonene, caryophyllene oxide and caryophyllene in the inflorescences oil caryophyllene oxide, limonene and crypton and in the resin oil bicyclo[3.1.1]hept -2-ene, 2,6,6- trimethyl- (52.82%), longifolen, crypton and Î²-pinene. Key words: Pinus caribaea, Chemical composition, Essential oil, GC-MS doi:10.3329/bjb.v37i2.1735 Bangladesh J. Bot. 37(2): 211-212, 2008 (December)